Case Report: Clinicopathological findings of a cutaneous mast cell tumor in a young domestic meerkat (Suricata suricatta) - Castaman, Marco Graziano; Orlandi, Margherita; Baldin, Martina; Massaro, Maria; Ridolfi, Mattia; Zambelli, Maristella (Frontiers in Veterinary Science, 2025)
A 10-month-old female domestic meerkat (Suricata suricatta) was presented with a cutaneous nodule in the left axillary region. The animal was clinically healthy and radiographs showed no evidence of involvement of visceral organs. Based on fine-needle aspirate that revealed numerous well-differentiated mast cells, a mast cell tumor was suspected. Surgical excision was performed and the mass submitted for histologic examination. Histopathological findings showed a round cell tumor, with marked cellular atypia and moderate mitotic activity; Giemsa special staining revealed a large number of fine cytoplasmic metachromatic granules. Histological and histochemical findings confirmed the cytological suspicion of a mast cell tumor. Based on prognostic factors used in the canine species, immunohistochemistry with antibodies against Ki67 (a marker of cellular proliferation) and CD117 (a KIT receptor localization marker) revealed that 90% of the neoplastic population was positive for CD117 (with a membranous staining pattern), and the Ki67 index was 28. The patient did not show local recurrence and sign of distant metastases at the 10 months follow-up. Based on literature search no previous reports of mast cell tumour in meerkats were retrieved. Therefore, this case highlights a previously undocumented presentation of mast cell tumor in this species, contributing to the expanding knowledge of neoplastic conditions in exotic companion animals.